Work-Life Balance and Job Performance of State Auditors in Southern Luzon, Philippines - Baluran, Angel L.; Palic, Annabelle S. (Technium Social Sciences Journal, 2025)
Work-life balance remains a continuous concern in every workplace due to its influence on employee performance. Hence, this study determined the extent of the work-life balance of state auditors in Southern Luzon in terms of self-management, time management, stress management, and leisure management relative to age, length of service, and audit sector. Additionally, it assessed the level of job performance as to quality, efficiency, and timeliness. Likewise, the work-life balance and job performance were compared when grouped according to demographics. Lastly, it ascertained the relationship between the two variables. This study utilized a quantitative research design, which combined descriptive, comparative, and correlational methods. It was responded to by 119 state auditors and was determined using stratified random sampling. Adapted survey questionnaires were administered for work-life balance, while secondary data were used for job performance. The collected data were then analyzed using the mean, standard deviation, frequency count, percentage distribution, Mann-Whitney U test, Kruskal-Wallis H test, post hoc test, and Spearman rank correlation. Meanwhile, the researcher adhered to the guidelines set forth by the Philippine Health Research Ethics Board (PHREB). The results indicated a great extent of work-life balance and an outstanding level of job performance. Significant differences in overall work-life balance, time management, stress management, and leisure management were found based on the respondents' audit sector, and overall job performance, quality, and efficiency were observed based on age and length of service. Interestingly, there was no significant relationship between work-life balance and job performance. However, while the level of job performance is commendable, the extent of work-life balance still has potential for improvement, highlighting the crucial role of a government audit institution in improving the work-life balance and maintaining job performance through a development plan.